Peranan Advokat Dalam Pemberian Bantuan Hukum kepada Orang yang Tidak Mampu Berdasarkan UU No 16 Tahun 2011 tentang Bantuan Hukum - Dhea Kinanty; Pramestia Andini Putri; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Free legal assistance is one of an Advocate's most important responsibilities. Every Advocate is required by Clause 56 of the Criminal Law Procedures section to provide low-income clients with free legal representation. The fundamental obligation to provide free legal assistance is Equality Before the Law.